(untitled) (IEM Journal, 2024)
In this study, adsorption isotherm experiments were used to study ammonium adsorption by surface bed sediments in the Loughor Estuary, South Wales. The findings indicated that the adsorption isotherm was linear and fitted the Freundlich adsorption isotherm, K*. The adsorption coefficient of ammonium in the study area ranged from 9.3 to 18 ml/g and the dimensionless ammonium adsorption coefficient was found to be ranged between 23.0 and 36.5. These values correlated well with the organic carbon content, of the sediments and can be considered as the main factors controlling ammonium sorption. The results also showed that salinity affected the adsorption of ammonium and the distribution of ammonium between the sediments and the water column. The amount of ammonium adsorption on the sediments was found to decrease gradually with the increment of the salinity levels.